Diagnostic performance of morning serum cortisol as an alternative to short synacthen test for the assessment of adrenal reserve; a retrospective study. Issue 1156 (29th October 2020) - Kumar, Rajeev; Carr, Peter; Wassif, Ws
Abstract: Objective: The short synacthen test (SST) is widely used across the UK to assess adrenal reserve. The main objective of our study was to determine the morning serum cortisol level that will predict adrenal insufficiency (AI) thus reducing our reliance on SST. Design: This was a single centre retrospective study of 393 SST tests measuring 0 and 60 min cortisol levels after administration of 250 μg of synacthen (synthetic ACTH). Patients and methods: All the SST tests for patients suspected of primary or secondary AI between April 2016 and October 2018 were included in this study. We used serum to determine circulating cortisol by a newer generation competitive electrochemiluminescence immunoassay (ECLIA) (Roche Diagnostics). A post-ACTH cortisol response of ≥420 nmol/L at 60 min was considered adequate to rule out AI. The data were analysed to ascertain the relationship between 0 min and 60 min serum cortisol. Results: A total of 393 SST results were included in this study. Overall, a total of 332 (84.5%) subjects achieved sufficient serum cortisol level at 60 min, while 61 subjects (15.5%) showed insufficient response. Using the logistic regression, we determined that a morning basal serum cortisol level of ≥354 nmol/L was able to predict normal adrenal function with 100% sensitivity. We were unable to find a lower cut-off value below which SST will not be required. By using this proposed cut-off point, approximately 37% of the SSTs tests could be avoided. Conclusions: Basal morning serum cortisol can be safely used as a first step in the evaluation of patients with suspected AI. This will enhance the number of patients being screened for this condition.